DESIGN OF A TESTING SYSTEM FOR THE STRETCHABILITY OF MOZZARELLA CHEESE USING THE DESIGN FOR SIX SIGMA (DFSS) METHOD - Utama, Made; Oktavianty, Oke; Darmawan, Zefry (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
Abstract This research was driven by the growing demand for mozzarella cheese and the need for better quality control, especially in testing its stretchability. Current manual methods like the fork test are subjective and inconsistent. To address this, the study aimed to design a simple, cost-effective, and user-friendly stretchability testing system using the Design for Six Sigma (DFSS) approach, which includes the Define, Measure, Analyze, Improve, and Verify stages. In the Define stage, interviews with CV Narendra Food and PT Greendfields Indonesia revealed current testing practices involve heating cheese at 160°C for 6 minutes and visually assessing its stretch. Key challenges include inconsistent heating and measurement variation. Users expressed the need for an automatic, consistent, and safe testing system made from food-grade materials like stainless steel 304, with added safety features and easy operation. In the Measure stage, user needs were prioritized through questionnaires and translated into technical requirements using a House of Quality (HoQ). A FAST Diagram was also used to identify primary and supporting functions. The Analyze stage produced eight design concepts using a morphology chart, evaluated based on technical criteria and user needs. Concept 1 was selected as the best design, featuring two-way pulling, convection-conduction heating, RTD PT100 sensors, and a stainless steel body. The design was modeled using SolidWorks, with components detailed and costs estimated. In the Verify stage, simulations tested and refined the design. User feedback on the 3D design was positive, noting its ease of use, safety, speed, and cost-effectiveness. Though users suggested a more compact size, they considered the machine highly suitable for both small and large-scale cheese production. Ultimately, the system offers a semi-automated, efficient, and standardized alternative to manual testing methods in the mozzarella cheese industry.